2019
DOI: 10.3390/ma12091434
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Properties of Hydrogen Peroxide Activated Crumb Rubber and Its Influence on the Rheological Properties of Crumb Rubber Modified Asphalt

Abstract: Crumb rubber modified (CRM) asphalt binder has been affirmed to improve resistance to rutting, moisture susceptibility, low-temperature cracking, and asphalt durability. However, CRM has poor compatibility with asphalt since crumb rubber molecules are vulcanized. The objective of this study was to develop a new method to prepare activated crumb rubber using hydrogen peroxide (H2O2) solution and to explore the rheological properties of H2O2 activated CRM (ACRM) asphalt. Three different percentages of H2O2 solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The impact of H 2 O 2 and KMnO 4 treatment on the morphology of GTR is presented in Figure 3. Compared to unmodified GTR, the surface of H 2 O 2 is more developed [34], however, it does not change significantly with the higher content of the applied modifier. It is in line with hydroxyl numbers determined for GTR:H 2 O 2 2:1, GTR:H 2 O 2 1:1 and GTR:H 2 O 2 1:2.…”
Section: Changes In Gtr Structurementioning
confidence: 84%
“…The impact of H 2 O 2 and KMnO 4 treatment on the morphology of GTR is presented in Figure 3. Compared to unmodified GTR, the surface of H 2 O 2 is more developed [34], however, it does not change significantly with the higher content of the applied modifier. It is in line with hydroxyl numbers determined for GTR:H 2 O 2 2:1, GTR:H 2 O 2 1:1 and GTR:H 2 O 2 1:2.…”
Section: Changes In Gtr Structurementioning
confidence: 84%
“…The movement of rubber molecules is thus limited, which makes the rubber surface inert. This cross-linked structure makes the compatibility between rubber and asphalt worse [21,22]. In addition, more than 20 wt.% carbon black is added into tires to improve tire strength, so a large number of inorganic materials such as carbon black were fixed in rubber molecules, and the compatibility between rubber powder and asphalt was further weakened [23].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the activation of rubber enhanced its interaction with asphalt binder and the storage stability of asphalt rubber was improved [ 30 ]. In additional, activation of rubber by hydrogen peroxide (H 2 O 2 ) solution [ 31 ] and plasma technology [ 32 ] are also effective way to improve the storage stability of modified asphalt binder. At present, research on improving storage stability through the activation of rubber powder mainly focuses on the evaluation of the macroscopic performance of asphalt binder, but the research on the microscopic performance is insufficient.…”
Section: Introductionmentioning
confidence: 99%